2023
DOI: 10.1021/acsanm.2c04913
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced and Stem-Cell-Compatible Effects of Nature-Inspired Antimicrobial Nanotopography and Antimicrobial Peptides to Combat Implant-Associated Infection

Abstract: Nature-inspired antimicrobial surfaces and antimicrobial peptides (AMPs) have emerged as promising strategies to combat implant-associated infections. In this study, a bioinspired antimicrobial peptide was functionalized onto a nanospike (NS) surface by physical adsorption with the aim that its gradual release into the local environment would enhance inhibition of bacterial growth. Peptide adsorbed on a control flat surface exhibited different release kinetics compared to the nanotopography, but both surfaces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
0
0
Order By: Relevance
“…aureus quantified from images in Figure C,D (* p < 0.05 and ** p < 0.005 compared with control, # p < 0.05 and ## p < 0.005 compared with nanoripple). (C, D) Comparison of antibacterial effect with previous papers; PLA, silk, DGEBA nanopatterns, ZnO, PC, PEEK nanopillars, black Ti, and TiO 2 nanospikes. ,,, (E) Schematic illustration of the mechanism of multifunctional nanopillar surface.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…aureus quantified from images in Figure C,D (* p < 0.05 and ** p < 0.005 compared with control, # p < 0.05 and ## p < 0.005 compared with nanoripple). (C, D) Comparison of antibacterial effect with previous papers; PLA, silk, DGEBA nanopatterns, ZnO, PC, PEEK nanopillars, black Ti, and TiO 2 nanospikes. ,,, (E) Schematic illustration of the mechanism of multifunctional nanopillar surface.…”
Section: Resultsmentioning
confidence: 98%
“…Figure C,D illustrates previous efforts to improve the antibacterial properties and cytocompatibility on various surfaces. ,,, , These studies evaluate the antibacterial properties of Gram-negative (E. coli and P.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surfaces with nanometer-scale concavo–convex structures, such as nanopillar arrays, exhibit antimicrobial properties and are expected to have various applications as drug-free antimicrobial surfaces. Several methods, including reactive-ion etching, nanoimprinting, and chemical vapor deposition, have been used to fabricate microstructure-based antimicrobial surfaces. However, the relationship between the antimicrobial properties and surface structures has not yet been clarified. To realize the fabrication of surfaces with higher antimicrobial properties, it is important to elucidate the effects of surface structures on antimicrobial properties.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that introducing high aspect ratio nanoscale topographies on Ti can confer antibacterial properties in vivo and in vitro while allowing mesenchymal stromal cell (human, hMSC) growth. 7,8 Additionally, studies have shown that bacteria are less likely to adhere to high aspect ratio nanostructured Ti compared to smooth surfaces. 9−11 First, this is because increased high aspect ratio features provide fewer contact points for bacterial adhesion as they rely on the physical interactions between their outer structures and the surfaces they colonize.…”
Section: ■ Introductionmentioning
confidence: 99%